Adapting to environmental and technological transformations through knowledge creation: insights from artisanal and small-scale gold mining in Tanzania - Tomassi, Oliver Daniel; Kinyondo, Abel Alfred; Jauhiainen, Jussi S. (Elsevier BV, 2026)
Artisanal and small-scale gold mining (ASGM) is a key economic sector in Tanzania and the Global South. Its predominant extraction method, mercury amalgamation, is valued for low cost and minimal skill requirements but poses severe risks to human health and the environment. ASGM is undergoing two major transformations: depletion of easily accessible deposits and growing mechanization. Cyanide leaching has emerged as a prominent alternative to mercury, promoted as a less harmful option yet still associated with significant environmental and health risks.
This study situates mercury and cyanide in ASGM within the Geography of Sustainability Transitions (GeoST) to examine how changes in the natural environment like mineral exhaustion influence extraction processes and sustainability. We adopt knowledge creation processes as an analytical lens to explore how miners develop and apply knowledge to adapt to transforming environmental and technological contexts.
Using a mixed-methods approach combining qualitative interviews and a quantitative survey conducted in Tanzania, we find that more efficient and relatively less environmentally harmful practices require complex knowledge of the natural environment and technologies that go beyond the sensory-based, experiential learning typical of mercury amalgamation. This knowledge gap sustains mercury use and exacerbates inequalities between miners with and without technical expertise. Our findings highlight the importance of linking knowledge creation with environmental conditions to support transitions away from highly unsustainable practices like mercury in ASGM.